The Effect of Warming Up with Estafet Ball Game Method on Student's Interest in Learning PJOK - Firdaus Manah Wangi Faruk; Heni Yuli Handayani; Khoirul Anwar; Septyaningrum Putri Purwoto (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine The Effect of the Warming Up with Estafet Ball Game Method on Student's Interest in Learning PJOK, this type of research is experimental with a quantitative approach, the total sample is 55, namely the experimental sample of 28 students and a sample of 27 students at SDN Batah Barat 2. The instrument is playing an interaction of the ball game and getting a questionnaire. Analyst data uses validity which is said to be valid because the value of r-table > 0,361 and reliability is said to be reliable because it is greater than 0,05. Then the big data analysis technique uses a prerequisite test more than the normality test with a normal distribution because it is greater than 0,05. Namely the experiment with the result of 0,680 and the control class 0,290. The homogeneity test is said be homogeneous because 0,793 > 0,05. And test the hypothesis using an independent t-test. Based on the independent t-test, there is no significant effect because the value obtained is 0,897. This means that H0 is rejected in the warm-up method of the estafet ball game, and the interest in learning PJOK has no significant effect.